AB0092 Sideritis Scardica Extract Prevents Bone Loss in Ovariectomized Rats. (9th June 2015) - Jeremic, I.; Petrovic, D.; Zivkovic, M.; Petricevic, S.; Tadic, V.; Petronijevic, M.; Stanojevic, Z.; Trajkovic, V.; Sefik-Bukilica, M.; Gosic, K.; Isakovic, A.
Abstract : Background: Osteoporosis is the most common metabolic bone disease. Postmenopausal loss of estrogen is a major risk factor. Objectives: To assess if total ethanolic extract of Sideritis scardica could prevent osteoporosis in ovariectomized female rats. Methods: Female Wistar rats were divided in three groups: I-sham operated (control), II-ovariectomized-OV and III-ovariectomized, treated orally with S.scardica extract (300 mg/kg) during 20 weeks-OVT. In 18th experimental week oral glucose tolerance test has been performed, as well measurement of bone mineral density-BMD. After killing, femurs, plasma and erytrocytes were isolated. The following parameters were measured: morfometric bone parameters, wet and dry bone mass, biomechanical testig (three point flexural test), Ca and P in urine and plasma, alkaline phosphatase in plasma, malondialdehyde, catalase activity, reduced gluthation (GSH), total SH groups, free fatty acids and fructozamines. Results: There was no significant difference in Ca and P concentration in plasma between groups, but urinary Ca and P were significantly higher in OV rats (Ca 0.67±0.24 mM, P 3.29±0.77 mM) in comparison to control (Ca 0.434±0.21 mM, P 2.32±1.00 mM) and OVT group (Ca 0.52±0.19 mM, P 2.89±0.42 mM) (p<0.05). Osteocalcin levels were higher in OV group than in control and OVT group, while ALP was higher in OVT group in comparison to OV and control group. OV rats had decreased proximal width of femoral neck (7.38±0.45 mm) in comparison to control (7.55±0.51mm), while OVT group had even greater width than control group (7.73±0.38mm) (p<0.05). OV animals had lower BMD on spine, hip, pelvis, legs and total BMD in comparison to control group, while treated animals did not have different BMD from control. Ultimate load was for control 3930, 6±82.4 N/m 2, for OV group 2726.68±93.4 N/m 2 and for OVT group 3257.2±86.5 N/m 2 (p<0.01). The ratio between wet and dry bone mass 77.97% in control, 72.81% in OV and 75.28% u OVT group. OVT rats showed much better oral glucose tolerance in comparison to control and OV group (p<0.05) and oxydative stress parameters was significanty better in OVT than in OV group (lower MDA, higher catalase, SH groups and GSH). Free faty acids and fructozamines also were lower in OVT than in OV group (p<0.05). Conclusions: S. scardica extraxct prevents bone loss in ovariectomized rats, increases bone resistance to mechanical load and reduces cardiovascular metabolic risc factors associated with menopause. Disclosure of Interest: None declared